A Harmonized Nitrous Oxide (N2O) Ocean Observation Network for the 21st Century - Bange, Hermann W.; Arévalo-Martínez, Damian L.; de la Paz, Mercedes; Farías, Laura; Kaiser, Jan; Kock, Annette; Law, Cliff S.; Rees, Andrew P.; Rehder, Gregor; Tortell, Philippe D.; Upstill-Goddard, Robert C.; Wilson, Samuel T. (Frontiers in Marine Science, 2019)
1. Abstract Nitrous oxide (N2O) is an important atmospheric trace gas involved in tropospheric warming and stratospheric ozone depletion. Estimates of the global ocean contribution to N2O emissions average 21 % (range: 10 to 53 %). Ongoing environmental changes such as warming, deoxygenation and acidification are affecting oceanic N2O cycling and emissions to the atmosphere. International activities over the last decades aimed at improving estimates of global N2O emissions, including (i) the MarinE MethanE and NiTrous Oxide database (MEMENTO) for archiving of quality-controlled data, and (ii) a recent large-scale inter-laboratory comparison by Working Group 143 of the Scientific Committee on Ocean Research (SCOR). To reduce uncertainties in oceanic N2O emission estimates and to characterize the spatial and temporal variability in N2O distributions in a changing ocean, we propose the establishment of a harmonized N2O Observation Network (N2O-ON) combining discrete and continuous data from various platforms. The network will integrate observations obtained by calibrated techniques, using time series measurements at fixed stations and repeated hydrographic sections on voluntary observing ships and research vessels. In addition to exploiting existing oceanographic infrastructure, we propose the establishment of central calibration facilities in selected international laboratories to improve accuracy, and ensure standardization and comparability of N2O measurements. Final data products will include a harmonized global N2O concentration and emission field for use in model validation and projections of future oceanic N2O emissions, to inform the global research community and policy makers.